Arabic Language Learning Planning at the Elementary School/Madrasah Ibtidaiyah Level: Ibnu Jarir Qur’an and Arabic School - Hana Yulia; Ade Kosasih; Muntazhar Nur Syabana (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Designing a plan for Arabic language learning is the first step toward achieving learning objectives. One measure of success in teaching is careful planning. The purpose of this study is to reveal the Arabic language learning plan at the Al-Qur'an and Arabic Language School Ibnu Jarir for elementary/MI levels. A qualitative method was applied in this study. Data were collected using observation, interviews, documentation, and literature review techniques. The results of the analysis of the planning stage in this study included an analysis of student conditions, learning objective design, document preparation, application of approaches, strategies, methods, and media, as well as an evaluation of learning planning. The findings indicate that the learning plan is systematically structured. It is based on an analysis of student conditions with classes divided according to learning styles and skill levels. Learning is dominated by interactive strategies using deep learning methods, but the details of the planning documents have not been fully compiled. Synergy in the planning process between educational institutions, parents, and students is essential to support active and effective Arabic language learning. This research contributes to teachers, researchers, and Arabic language educational institutions in developing optimal learning plans to meet student needs.